The Leadership Model of Reje in Preserving The Customs and Cultural Identity of The Gayo Ethnic - Syahputra, Muhammad Rizki; Rifa'i, Muhammad; Chaniago, Nasrul Syakur; Zendah, Ali Abedlqader Ali (Idarah (Jurnal Pendidikan dan Kependidikan), 2025)
This study investigates the role of Reje leadership in preserving the customs and cultural identity of the Gayo community in Kampung Keramat Mupakat. Utilizing a descriptive-analytical qualitative approach, the research examines the meanings, values, and practices of Reje leadership across four dimensions: religious, justice, cultural, and participatory. Data were collected through in-depth interviews, participatory observations, and the review of customary documents, and analyzed using the Miles, Huberman, and Saldaña model. The findings reveal that Reje leadership is grounded in the principle of ("customs based on sharia, sharia based on the Qur'an"), affirming the spiritual legitimacy of Gayo traditions. The justice dimension is reflected in deliberative consensus, ensuring inclusive, fair, and widely accepted decisions, thereby strengthening social harmony. The cultural dimension highlights the Reje's efforts to preserve local traditions such as melengkan, kenduri keramat, and the use of the Gayo language which are transmitted to younger generations as safeguards of identity. The participatory dimension emphasizes the inclusivity of Reje leadership through the involvement of customary, religious, and community leaders in every significant decision. Collectively, these four dimensions demonstrate that Reje leadership functions as a mediator of customary and Islamic values, a guardian of traditions, and an agent of cultural education. The study concludes that the Reje leadership model remains relevant and strategic in safeguarding Gayo customs and cultural identity amid the challenges of modernization, while also contributing significantly to academic discourse on leadership rooted in local wisdom in Indonesia.